The Farm Bill: Helping Landowners Help Wildlife - Kristin C. Thomas; William M. Giuliano (EDIS)
The United States Department of Agriculture administers a wide variety of Farm Bill programs through the Natural Resources Conservation Service (NRCS), the Farm Service Agency (FSA), and the Forest Service (FS). A good place to start is a phone call to your local NRCS service representative, county extension agent, or county forester to find out which Farm Bill program best fits your land management goals. All of the programs have variable deadlines, specific eligibility requirements, and generally include the development and implementation of a land management plan. A brief summary of the available programs, followed by contact information, is listed in this document. This document is WEC 205 and one of a series of the Department of Wildlife Ecology and Conservation, UF/IFAS Extension. First published: January 2006.